The Non Standard English Used by Women in the Help Movie - Aal Inderajati; U Ubaidillah (IJEE (Indonesian Journal of English Education), 2016)
ABSTRACT This research discusses the grammatical features of Non-Standard English that is used by women characters in The Help movie and also the factors that influence it. The discussion in this research uses the theory from Trudgill (1999) and Holmes (1992). Further, SPEAKING formula proposed by Dell Hathaway Hymes (1974) is also used to determine the factors that influence the use of Non-Standard English. The study found five features of non-standard English used by women characters; they are missing auxiliary verbs, construction words, grammatical mistakes, wrong pronouns, and double negatives. Those features were found in the 108 data or conversations. The researcher analyzed those features through SPEAKING formula to find the factors. The factors which affect the use of non-standard English are Setting and Scene, Participants, Ends, and Genre. Moreover, Participants is the factor that mostly influences the use of Non-Standard English by women in The Help movie.   ABSTRAK Dalam penelitian ini akan dibahas tentang fitur-fitur gramatikal bahasa Inggris non-standard yang digunakan oleh karakter wanita dalam film The Help dan juga faktor yang mempengaruhi penggunaannya. Pembahasan dalam penelitian ini menggunakan teori dari Trudgill dan Holmes. Disamping itu, teori SPEAKING yang dikemukakan oleh Dell Hathaway Hymes juga akan digunakan untuk mengetahui faktor yang mempengaruhi penggunaan bahasa Inggris non-standard tersebut. Dari hasil analisis, peneliti menemukan lima fitur bahasa Inggris non-standard yang digunakan oleh karakter wanita; fitur tersebut yaitu missing auxiliary verb, construction words, grammatical mistakes, wrong pronoun, dan double negative. Faktor yang mempengaruhi penggunaan bahasa non-standard ialah Setting and Scene, Participants, Ends, dan Genre. Participants adalah faktor yang paling banyak mempengaruhi penggunaan bahasa Inggris nonstandard oleh karakter wanita dalam film The Help. How to Cite: Inderajati, A. Ubaidillah. (2016). The Non Standard English Used by Women in the Help Movie. IJEE (Indonesian Journal of English Education), 3(2), 106-122 doi:10.15408/ijee.v3i2.5509. Permalink/DOI: http://dx.doi.org/10.15408/ijee.v3i2.5509